Cost-effectiveness of interventions to control cardiovascular diseases and diabetes mellitus in South Asia: a systematic review - Singh, Kavita; Chandrasekaran, Ambalam; Bhaumik, Soumyadeep; Chattopadhyay, Kaushik; Gamage, Anuji Upekshika; Silva, Padmal De; Roy, Ambuj; Prabhakaran, Dorairaj; Tandon, Nikhil (BMJ Publishing Group Ltd, 2018)
OBJECTIVES: More than 80% of cardiovascular diseases (CVD) and diabetes mellitus (DM) burden now lies in low and middle-income countries. Hence, there is an urgent need to identify and implement the most cost-effective interventions, particularly in the resource-constraint South Asian settings. Thus, we aimed to systematically review the cost-effectiveness of individual-level, group-level and population-level interventions to control CVD and DM in South Asia.